2019
DOI: 10.1096/fj.201801218rr
|View full text |Cite
|
Sign up to set email alerts
|

A defective flexible loop contributes to the processing and gating defects of the predominant cystic fibrosis‐causing mutation

Abstract: People with the genetic disease cystic fibrosis (CF) often carry a deletion mutation ∆F508 on the gene encoding the CF transmembrane conductance regulator (CFTR) Cl− channel. This mutation greatly reduces the CFTR maturation process and slows the channel opening rate. Here, we investigate whether residues near F508 contribute to these defects in ∆F508‐CFTR. Most deletion mutations, but not alanine substitutions, of individual residues from positions 503 to 513 impaired CFTR maturation. Interestingly, only prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…Additional studies demonstrated that a single-residue deletion in the region 491-525 elicits an array of abnormalities in CFTR function [26]. Although it was found that specifically the amino acids V510 and S511 deletions did not cause problems in the processing of the CFTR protein, our data show that the new mutation S511Lfs*2 is caused by the deletion of two T nucleotides in different codons.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Additional studies demonstrated that a single-residue deletion in the region 491-525 elicits an array of abnormalities in CFTR function [26]. Although it was found that specifically the amino acids V510 and S511 deletions did not cause problems in the processing of the CFTR protein, our data show that the new mutation S511Lfs*2 is caused by the deletion of two T nucleotides in different codons.…”
Section: Discussionmentioning
confidence: 52%
“…3), which is responsible by the channel activation and thus essential for the functionality of the protein. The loss of this domain was predicted based on sequence and structural analysis, since this domain was not resolved by the Electron Cryomicroscopy (cryo-EM) structure [20,26].…”
Section: Discussionmentioning
confidence: 99%
“…CF-associated mutations diminish CFTR function primarily by reducing 1) mRNA synthesis, 2) protein expression, 3) channel regulation and 4) channel conductance, or by increasing 5) protein degradation at the cell membrane ( Amaral and Farinha, 2013 ). For example, the most prevalent CF mutation ΔF508 by introducing intrinsic structural flaws ( Chen et al, 2019 ) blocks CFTR protein expression at the cell membrane ( Cheng et al, 1990 ), whereas ΔF508, G551D and G1349D mutations greatly decrease channel activity ( Dalemans et al, 1991 ; Cai and Sheppard, 2002 ; Cai et al, 2006 ; Bompadre et al, 2007 ; Chen et al, 2009 ; Chen et al, 2017 ) with further alterations in channel responses to gating potentiators ( Hwang et al, 1997 ; Cai and Sheppard, 2002 ; Cai et al, 2006 ; Bompadre et al, 2007 ) and intracellular pH ( Chen et al, 2009 ; Chen et al, 2017 ). Therefore, the current drug therapy for CF aims to elevate the protein expression and channel activity of mutant CFTRs by correctors and potentiators, respectively ( Bose et al, 2020 ).…”
Section: The CL − Transport Defect and The High Sa...mentioning
confidence: 99%